KESALAHAN PEMAKAIAN BAHASA INDONESIA MEDIA LUAR RUANG DI KOTA TANGERANG SELATAN - Bram Denafri; Washadi Washadi (LPPM Universitas Bumigora Mataram, 2020)
This research is urgent to do considering the use of Indonesian outdoor media which is increasingly complex and uncontrolled. This issue has led to the development of a wide variety of written media in outdoor media whose rules deviate significantly from the Indonesian Spelling General Guidelines. The inconsistency between the rules and the use of various languages ​​will lead to the skepticism of Indonesian people to use Indonesian properly and correctly. Also, the development of the Indonesian language that is not based on good linguistic knowledge will lead to the erosion of the Indonesian language and irregular language growth. Therefore, this research is important to do to see patterns of Indonesian language mistakes in outdoor media. With the hope that the Indonesian Spelling Guidelines are applied in a basic and solid manner in the use of Indonesian outdoor media. This type of research is a descriptive study with a qualitative approach. This research tries to understand and explain the phenomena of misuse of the Indonesian language in outdoor media in South Tangerang City. This research produces descriptive data in the form of sentences in outdoor media in South Tangerang City. Sources of data in this study were obtained from written sources. Sources of written data were obtained from billboards, billboards, banners, billboards, and neon boxes.